(untitled) (Research, Society and Development, 2021)
Introduction: Candidiasis is related to a wide variety of clinical manifestations that are expressed from skin and mucosal infections to systemic infection. The latter being associated with a high global mortality rate, ranging from 36% to 63% in different groups of patients. The therapy of invasive fungal infections is limited, as there are only three classes of conventional drugs used. In this scenario, strategies for the rational use of antifungal agents and the search for new therapeutic alternatives are necessary. Objective: To evaluate the in vitro antifungal activity of the monoterpene dihydrojasmone against fluconazole resistant strains of Candida albicans and Candida parapsilosis. Methodology: The minimal inhibitory (MIC) and minimal fungicidal (MFC) concentrations were determined by the microdilution method. It was later observed whether the antifungal action of dihydrojasmone occurs via the cell wall (sorbitol assay) or via membrane (exogenous ergosterol assay). Results: Dihydrojasmone had a MIC between 128 - 256 µg/mL and MFC had the same MIC values, respectively. In the assay with exogenous ergosterol, the MIC of dihydrojasmone increased in the presence of exogenous ergosterol, suggesting that the mechanism of action of monoterpene occurs through its binding to ergosterol present in the membrane. There was no change regarding the use of sorbitol. Conclusion: Based on these results, the present study demonstrates that dihydrojasmone has strong antifungal activity, and suggests that this activity is related to its binding to ergosterol in the fungal membrane. Therefore, dihydrojasmone proves to be a promising bioproduct in the search for alternatives for the treatment of candidiasis.